TINJAUAN YURIDIS TERHADAP PENJATUHAN PIDANA DALAM KASUS PENGEDARAN KOSMETIK YANG TIDAK MEMILIKI IZIN EDAR: Studi Putusan Nomor 131/Pid.Sus/2024/PN Bau - Bunga Ali La Ode; Asri La Ode (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
This study discusses the imposition of criminal sentences in the case of distribution of cosmetics without a distribution permit based on Decision Number 131/Pid.Sus/2024/PN Bau. The purpose of this study is to determine whether the judge's decision is in accordance with the applicable laws and regulations in the health sector and to understand the basis for the judge's legal considerations in imposing a sentence. The research method used is a normative and empirical legal approach, with data collected through document studies and interviews. The results of the study indicate that the perpetrators were legally proven and promised to commit a crime as regulated in Article 435 in conjunction with. Article 138 paragraph (2) of Law Number 17 of 2023 concerning Health, and is subject to a prison sentence of 5 months. This criminal sentence is considered to be in accordance with Article 435 because the article does not regulate the minimum sentence imposed. The judge's considerations include elements of pardon, evidence of cosmetics without a distribution permit, and confessions. This decision is considered to have fulfilled the elements of legality, although further study is needed regarding the deterrent effect and aspects of consumer protection. This research is expected to contribute to law enforcement against violations in the health sector and strengthen supervision of the circulation of cosmetic products.